Manajemen Kanker Kolorektal di Rumah Sakit Umum Daerah Cut Meutia Aceh Utara Tahun 2021-2023 - Salmiah Salmiah; Muhammad Sayuti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Colorectal cancer is a disorder that occurs exclusively in the colon or rectum and is caused by the abnormal proliferation of intestinal glandular epithelial cells. This cancer is the second most cancer-related death worldwide. Around 9.4% of cancer-related deaths were caused by colorectal cancer in 2020. Routine examinations are very important for early detection and the prognosis of colorectal cancer also varies depending on the stage at diagnosis so that with good screening and management, the death rate from colorectal cancer can be reduced . This study aims to determine the management of colorectal cancer patients at the Cut Meutia Regional General Hospital. The type of research used is descriptive research with a cross sectional design. This research was conducted at Cut Meutia Regional Hospital in August 2023-September 2023. The population and sample used was 27 people using total sampling as the sampling technique. The samples were selected according to the inclusion and exclusion criteria. The material used in this research is secondary data in the form of medical records taken from Cut Meutia Regional Hospital. The results of the research show that based on the characteristics of respondents, the gender that most suffers from colorectal cancer is women compared to men, in terms of age, the majority are in late adulthood and work as housewives. Based on the location of the cancer, the most common is Adeno Ca Recti. Based on the results of anatomical pathology examination, the most common is Adeno carcinoma well differentiated. Based on the type of procedure most often performed is laparotomy. Based on chemotherapy status, patients more often did not receive chemotherapy and based on radiation therapy status, patients also more often did not receive radiation therapy.